2001
DOI: 10.1126/science.1062883
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Self-Organization in a Surface Reaction: From the Atomic to the Mesoscopic Scale

Abstract: Scanning tunneling microscopy data revealed the atomic processes in propagating reaction fronts that occur in the catalytic oxidation of hydrogen on Pt(111). The fronts were also characterized on mesoscopic length scales with respect to their velocity and width. Simulations on the basis of a reaction-diffusion model reproduce the experimental findings qualitatively well. The quantitative comparison reveals the limitations of this traditional approach to modeling spatiotemporal pattern formation in nonlinear dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(117 citation statements)
references
References 19 publications
4
111
0
2
Order By: Relevance
“…This approach has produced outstanding results in different fields, such as solid-state chemistry or catalysis 21 . The environmental parameters in our simulation chambers, such as temperature, vacuum and gas composition, were as close as possible to the conditions occurring in the CSE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has produced outstanding results in different fields, such as solid-state chemistry or catalysis 21 . The environmental parameters in our simulation chambers, such as temperature, vacuum and gas composition, were as close as possible to the conditions occurring in the CSE.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of surface science methodology to mimic and characterize the essential characteristics of complex problems concerning molecules on surfaces has been previously demonstrated by explaining, among others, the fundamentals of catalysis 21 or the formation of H 2 on the stardust grains 20 . We simulate the conditions of interstellar space using ultra-high vacuum (UHV) chambers equipped with in situ atom-resolved scanning tunnelling microscopy (STM) and third-generation synchrotron radiation-based X-ray photoemission-spectroscopy (XPS), among others.…”
mentioning
confidence: 99%
“…Alternatively, the chemical patterns could be produced by fabricating domains of catalyst on a surface that promote the production of fuel from reactions in the medium 36. Chemical patterns may have macroscopic to nanoscopic characteristic lengths, allowing systems with a wide range of length scales to be explored 37, 38, 39, 40, 41. When chemically propelled motors operate in such media new phenomena appear; for example, it has been shown that chemically propelled nanomotors can be reflected from traveling chemical fronts in media where cubic autocatalytic reactions take place 42…”
Section: Introductionmentioning
confidence: 99%
“…[2] In the past the in situ investigation of catalyst surfaces was difficult, because the most surface sensitive imaging and spectroscopy techniques were restricted to high vacuum conditions. [3,4] Recent instrumental developments however, have made possible the investigations at elevated pressures using imaging [5][6][7][8][9][10] and spectroscopic [11,12,13] methods, among them X-ray photoelectron spectroscopy (XPS) [14,15,16] that has been shown to be able to operate at pressures of up to 10 mbar. [17,18] Here we present the use of XPS at millibar pressures to determine the chemical species near the surface of a catalyst, including the gas phase reaction products, in situ, i.e.…”
Section: Introductionmentioning
confidence: 99%